Produktivitas Kolam Pembesaran Larva Nila Merah Dengan Tanah Dasar Inceptisol Yang Dimarel Bahan Ultisol Dan Vertisol - Hasibuan, Saberina (Jurnal Perikanan dan Kelautan, 2012)
A major constraint in the fish farming system in Yogayakarta, Indonesia, isthe low physical fertility of the pond bottom soil, which is made up of the sandyInceptisols. This study aimed to alleviate this constraint by physically mixing itwith Ultisols and Vertisols that have a higher clay content. The Inceptisols wasmixed with Ultisols (I-U) and Vertisols (I-V) with the proportion of (70:30), (50:50), and(30:70). These mixtures were then given basal fertilizer in the form of quaildroppings manure at a dose of 2 tons/ha/month, urea and super phosphate. The fishculture was divided into two systems: ponds with 50 fish/m2 and ponds without fish. Thebest mixture was 30% Inceptisols with 70% Ultisols and 50% Inceptisols with 50%Vertisols with basal fertilizer. These mixtures gave significant improvement inchlorophyll-a concentration, plankton diversity, benthic algae abundance, and fishgrowth.